On the Asymptotic Properties of Solutions of Linear Stochastic Differential Equations in R^d - Buldygin, V. V.; Koval, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We investigate necessary and sufficient conditions for the almost-sure boundedness of normalized solutions of linear stochastic differential equations in R^d their almost-sure convergence to zero. We establish an analog of the bounded law of iterated logarithm.